Detection of severe acute respiratory coronavirus virus 2 (SARS-CoV-2) in outpatients: A multicenter comparison of self-collected saline gargle, oral swab, and combined oral–anterior nasal swab to a provider collected nasopharyngeal swab. (13th November 2021) - Kandel, Christopher E.; Young, Matthew; Serbanescu, Mihaela Anca; Powis, Jeff E.; Bulir, David; Callahan, James; Katz, Kevin; McCready, Janine; Racher, Hilary; Sheldrake, Elena; Quon, Dorothy; Vojdani, Omid Kyle; et al.
Abstract: Background: Widespread testing for severe acute respiratory coronavirus virus 2 (SARS-CoV-2) is necessary to curb the spread of coronavirus disease 2019 (COVID-19), but testing is undermined when the only option is a nasopharyngeal swab. Self-collected swab techniques can overcome many of the disadvantages of a nasopharyngeal swab, but they require evaluation. Methods: Three self-collected non-nasopharyngeal swab techniques (saline gargle, oral swab and combined oral-anterior nasal swab) were compared to a nasopharyngeal swab for SARS-CoV-2 detection at multiple COVID-19 assessment centers in Toronto, Canada. The performance characteristics of each test were assessed. Results: The adjusted sensitivity of the saline gargle was 0.90 (95% CI 0.86-0.94), the oral swab was 0.82 (95% CI, 0.72–0.89) and the combined oral–anterior nasal swab was 0.87 (95% CI, 0.77–0.93) compared to a nasopharyngeal swab, which demonstrated a sensitivity of ˜90% when all positive tests were the reference standard. The median cycle threshold values for the SARS-CoV-2 E-gene for concordant and discordant saline gargle specimens were 17 and 31 ( P < .001), for the oral swabs these values were 17 and 28 ( P < .001), and for oral–anterior nasal swabs these values were 18 and 31 ( P = .007). Conclusions: Self-collected saline gargle and an oral–anterior nasal swab have a similar sensitivity to a nasopharyngeal swab for the detection of SARS-CoV-2. These alternative collection techniques are cheap and can eliminate barriers to testing, particularly in underserved populations.